Proposta de um modelo de gestão de custos para pequenas propriedades rurais familiares com foco na tomada de decisão - Lizot, Mauro (2016)
This work was general-purpose, develop a proposal of a theoretical model of decisionmaking with a focus on management of small family farms costs, which enables support for decision making. And the following objectives: i) develop a structured methodology, which allows to form a literary basis to provide scientific support for the implementation of research; ii) develop based on the literature the dimensions and variables of the necessary models to propose an application and iii tooling) to implement the proposed model within the dimensions and variables, and validate every stage background and perform the necessary conclusions to verify the effectiveness of applied model. In terms of methodology, we used a structured methodology, which allowed forming a bibliographic portfolio of 29 articles, and through the research constructs developed, based on an existing model, an activity segmentation model for aid farmer of small family farms in the decision-making process with emphasis on cost management. The model was applied in six family farms in the South West region of Parana and Santa Catarina West. With regard to the search results, it was identified that the model can be applied to the specific context for which it was created. It was also possible to identify that the proposed model was valid and relevant to aid in the management of family farms by identifying, through the targeting of productive activities, investment priorities guided by the balance between managing costs and return activities. Moreover, possible to target the activities of six surveyed properties, demonstrating that the property 02, has the shape of more complex segmentation should be divided into three groups of activities, which can be conducted in parallel without any restrictions between activities. Other properties have the segmentation of the simplest activities, allowing viewing in this way that there are activities of groups that require prioritizing investments. Specifically the property 01 and 04 have the highest priority investment target groups, the most prominent activities of groups representing respectively 49.32% and 47.40%, which are represented by grain production activities on the property 01 and grain production, beef cattle and eggs on the property 04.